2020
DOI: 10.1371/journal.pone.0233244
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal principal component analysis to identify major features of white matter structure and links to reading

Abstract: The role of white matter in reading has been established by diffusion tensor imaging (DTI), but DTI cannot identify specific microstructural features driving these relationships. Neurite orientation dispersion and density imaging (NODDI), inhomogeneous magnetization transfer (ihMT) and multicomponent driven equilibrium single-pulse observation of T1/T2 (mcDE-SPOT) can be used to link more specific aspects of white matter microstructure and reading due to their sensitivity to axonal packing and fiber coherence … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 59 publications
9
59
0
Order By: Relevance
“…Our finding suggests that myelin content is unlikely to be driving the associations between FA and reading in FT children. While myelin content may be associated with maturity and transmission efficiency, it appears not to be the principal factor associated with individual differences in reading in FT born individuals, based on the results in this study and those in related work (Geeraert et al, 2020). These findings are consistent with studies that report negative associations of FA and reading (Dougherty et al, 2007;Odegard et al, 2009;Travis et al, 2016), because myelin content is likely to cause positive FA associations, not negative ones.…”
Section: Correlations Between Reading Abilities and White Matter Metricssupporting
confidence: 84%
See 2 more Smart Citations
“…Our finding suggests that myelin content is unlikely to be driving the associations between FA and reading in FT children. While myelin content may be associated with maturity and transmission efficiency, it appears not to be the principal factor associated with individual differences in reading in FT born individuals, based on the results in this study and those in related work (Geeraert et al, 2020). These findings are consistent with studies that report negative associations of FA and reading (Dougherty et al, 2007;Odegard et al, 2009;Travis et al, 2016), because myelin content is likely to cause positive FA associations, not negative ones.…”
Section: Correlations Between Reading Abilities and White Matter Metricssupporting
confidence: 84%
“…Our team has reported that values of R1 in the cerebellar peduncles were related to reading abilities in FT children (Bruckert et al, 2020). A recent study showed, however, that two brain imaging metrics of myelin content in cerebral tracts were associated with age but not with reading abilities in typically developing FT children (Geeraert et al, 2020). A gap in the literature is whether reading abilities in FT and PT children would show similar or different patterns of associations with metrics sensitive to myelin content in cerebral white matter pathways, as they do with diffusion metrics.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Interestingly, our PCA yielded combinations of diffusion measures that differed from those of two prior studies that have used this approach. 30,47 These prior studies used samples of typically-developing children without neurological insults and found similar PCs. To the extent that the PCs reported in these prior studies reflect healthy neurotypical brains, our PCs suggest that our concussed sample was not as similar in white matter structure to healthy controls as expected.…”
Section: Discussionmentioning
confidence: 80%
“…While we observed significant univariate associations of tau to NDI and ODI, these indices’ contribution was minimized when considered in a multivariate context. This, however, may not be the case for healthy younger adults or when only considering a sample of healthy aging individuals where pathology is less salient, though it remains unclear since multivariate multimodal imaging is not yet routinely applied to NODDI outputs(though see 53 ) and future studies are warranted.…”
Section: Discussionmentioning
confidence: 99%